Volunteer sport coaches and their learning dispositions in coach education - Griffiths, M. A.; Armour, K. M. (International Journal of Sports Science and Coaching, 2013)
There is agreement in the literature that dispositions act as mediating factors in directing the cognitions of individuals. In the context of coach professional development, dispositions direct and energise individuals' interpretations and actions as they engage in a range of learning situations. Drawing data from a study that examined the professional development of 19 volunteer coaches and 2 coach educators in one region of the UK, this study sought to elicit an understanding of coaches' dispositions towards coach learning. Findings indicated that coaches' dispositions of intentionality (e.g., inquisitiveness, attentiveness and open-mindedness) and reciprocity (e.g., readiness to engage with others, ask questions, willingness to accommodate alternative perspectives) arbitrated their engagement with any formal development activity. There is, therefore, a clear role for coach educators and governing bodies to consider how materials, pedagogies and assessment tools are developed that serve to facilitate, confirm or challenge coaches' learning dispositions towards professional development activities.